Unilateral Measures and Emissions Mitigation - CHATTERJI, Shurojit (Institutional Knowledge at Singapore Management University, 2010)
We discuss global climate mitigation that builds on existing unilateral measures to cut emissions. We document and discuss the rationale for such unilateral measures argue that such measures have the potential to generate positive spillover effects both within and across countries. In a simple dynamic model of learning we show that while single countries on their own may never get to the point of switching completely to low emission activities, a learning process with positive spillovers across nations is more likely to deliver a global switch to low emissions. We discuss the key features of a new global Intellectual Property (IP) regime that builds on the positive spillovers inherent in unilateral initiatives and accelerates global convergence to low emissions.